Language choice among Malaysian Tamil Youth / Pawathy Nalliannan - Pawathy , Nalliannan (2019)
Although some studies have shown that there is a pattern of language shift to English among Malaysians of Tamil descent, Tamil continues to be used as a first language by the majority of Malaysian Tamils. Whilst studies on the Tamil community tend to focus on language maintenance and shift, there is a dearth of studies looking at language choice among the younger generation of Malaysian Tamils in intra-group communications within a multilingual context. Thus, this study looks at the language choice of a group of Tamil youth in Malaysia. Previous studies have shown that domains of language use and social network play important roles in the patterns of language choice. This study, therefore, employs Fishman’s (1972) domain model to explore the language choices in intra-group communication. Data were collected through 109 respondents, supplemented with audio-recordings of natural conversations from 42 of them. Interviews with 40 of the respondenrs were carried out to obtain in-depth information on patterns of language use and to confirm the reasons for the languages used. The findings revealed that in four of the seven domains, Tamil is used more frequently although it is mixed with English and Malay expressions. The domain of family shows a relatively higher use of Tamil. However, the use of Tamil with grandparents, parents, siblings and children (for married participants) appears to be decreasing among the four generations. The domains of education, workplace and transaction show language shift towards English and Malay. In addition, married participants seem to be shifting towards English as they see it as being important for their children’s future. The findings also revealed the use of a different variety of spoken Tamil among the youth. The use and influences of English and Malay appear to have an effect on the use of socially appropriate varieties of Tamil among the youth.